CHRISTOLOGICAL: THE PHENOMENAL FIGURE FULL OF CONTROVERSIES - Ineke Marlien Tombeng (SOSIOEDUKASI, 2025)
This study aims to explore and analyze the development of views on Jesus Christ from both historical and theological perspectives, and to assess their relevance for contemporary Christian life. This research employs a qualitative approach, utilizing literature review and hermeneutic analysis to understand the manifestation and meaning of Jesus across various historical and theological contexts. Data is gathered through the examination of biblical texts, church documents, and theological literature from Christian thinkers throughout history. The analysis is conducted thematically to identify key themes in the understanding of Jesus, ranging from His identity as the Jewish Messiah to His significance in modern and postmodern Christian theology. The findings indicate that, despite the many interpretations and controversies surrounding the historical Jesus and the Christ of faith, the core teaching of Jesus as the Savior remains steadfast. Efforts to reconstruct Jesus in the modern context—such as those by Reimarus, Strauss, Bultmann, and the Jesus Seminar—offer alternative perspectives, but the foundational ideas of Jesus' divinity and His role in human salvation remain central to Christian faith. Additionally, the study reveals that Jesus is not only relevant in historical or doctrinal contexts but also in the lived experience of believers amidst current social and moral challenges. This research emphasizes the need for a more holistic and contextual approach to understanding Jesus Christ, helping Christians connect His teachings to contemporary issues such as justice, solidarity, and human dignity. It also highlights the importance of dialogue between theology, history, and culture in maintaining the relevance of Christian faith in a pluralistic and globalized world. Consequently, Jesus Christ remains the central figure of faith, not only doctrinally but also practically in the everyday lives of Christians worldwide.